Degree of development of rural tourism in Galicia: The complementary offer as the key to success - Cabaleiro Besada, Andrea; Araújo Vila, Noelia; Fraiz Brea, José Antonio (Revista Galega de Economía, 2019)
Rural tourism is a tourism model away from overcrowding, which takes place in rural countryside areas. The main objective of this investigation focuses on determining the development’s degree of rural tourism in Galicia and explain the most sought after complementary offer to this kind of tourism, seeking synergies with other companies in rural areas. For this, a theoretical framework on which work is established and then conducted in-depth interviews with industry experts and owners or managers of cottages of this region. Among the main conclusions is that virtually any type of complementary activity is compatible with this type of tourism, as long as it counts with support and appropriate actions.